A institucionalização organizacional do abastecimento de produtos hortigranjeiros no Brasil - Assumpção, Ricardo Chagas (1978)
A firsthand knowledge of the structure and ambiance of the National Food Supply Center System (SINAC) serves as the foundation for this article. Demonstrating a basic institutional approach, the analysis presented upholds the assertion that any modernization within the social sector Can be achieved by organizations which foster development. This paper's principal aim is to reveal the flow of the diverse transactions within the above-mentioned organization, the preponderant institutional variables and linkages, as well as the dysfunctions to be found in the organizational arrangements. In spite of the formal support given to this organization, its institutional involvement is minimal due to the ambiguity and incoherence of specific variables.The absence of any discip1inary measures, geared to cata1ytic and unifying ends and related to institutional and environmental variables, assembled within a realistic policy for the produce sector, substantiates conclusions that such an arrangement has created administrative-operational hindrances and has obstructed the institutionalization process of the National Food Supply Center System (SINAC). The recommendations offered center upon an organizational reformulation directed to the redefinition of objectives, propositions and implementation possibilities, with a basis in the tangible support of enabling linkages. Additional suggestions include an investment of personnel and research projects in the area of agricultural marketing, adopting a more pragmatic and less academic approach.